Kandungan Natrium Siklamat pada Manisan Buah dan Hubungannya dengan Pengetahuan dan Perilaku Penjamah Makanan Industri Pangan Rumah Tangga - Suparmi Suparmi; Rina Fauziah; Sri Mulyani (Journal of Telenursing (JOTING), 2023)
This study aimed to determine the levels of sodium cyclamate in candied fruit and to analyze the relationship between knowledge and behavior of food handlers in the Household Food Industry (IPRT). This research method is descriptive-analytic using a cross-sectional design. The research location was in Jambi City, and samples were tested in the Baiturahim Jambi STIKes Mathematics and Natural Sciences laboratory involving 50 selections for examining sodium cyclamate content and 35 food handlers at the candied fruit IPRT in Jambi City. Knowledge, behavior, and sodium cyclamate content data were analyzed using the chi-Square test. The results of the study were that of 35 IPRT food handlers, and there were 29 food handlers with high knowledge (82.9%), there were 21 food handlers with good behavior (60.%), 16 samples of candied fruit that were positive (≥ 3.00 mg/Kg). There is no relationship between knowledge and sodium cyclamate content in candied fruit, p-value > 0.05, and there is a relationship between food handler behavior and sodium cyclamate content, with p-value <0.05. The research concludes that there are still many sweets in Jambi City that contain positive sodium cyclamate and are related to the behavior of food handlers and not related to their behavior. Keywords: Candied Fruit, Sodium Cyclamate, Knowledge, Behavior